(untitled) (Annals of Medical Research, 2023)
Aim: Pemetrexed (PMTX) is a multi-targeted anticancer agent that exerts its antifolate effect by disrupting the folate dependent metabolic processes underlying cell proliferation. Kidney toxicity is a common side effect of anticancer agents. Chrysin (Chr) is a powerful antioxidant compound abundant in plant extracts, honey, and bee propolis. The aim of this study is to investigate the effect of the combined use of chrysin, a natural flavonoid, against the possible harmful effects of PMTX on kidney tissue. Materials and Methods: 50 Wistar albino male rats were divided; Control, Sham, PMTX, Chr, PMTX+Chr groups. Sham (1ml corn oil/day), Chr (50mg/kg/day) by oral gavage, PMTX (1mg/kg/week) by i.p., PMTX+Chr (PMTX;1mg/kg/week, Chr;50mg/kg/day) were given at the same time every day. At the end of 4 weeks of the study, kidney tissues and blood were collected. Creatinine (Cr) and blood-urea-nitrogen (BUN) analyzed in serum by ELISA. The malondialdehyde (MDA), superoxide dismutase (SOD) activities and total antioxidant status (TAS), total oxidant status (TOS), OSI also were measured in kidney tissue. Results: Indicators of oxidative stress, MDA was elevated and antioxidant activity was reduced in the PMTX groups compared to Control and Sham groups (p <0.05). In the PMTX+Chr group, MDA, BUN, Cr and TOS were decreased, SOD and TAS was increased compared to PMTX group (p <0.05). Conclusion: Chr exhibited ameliorative effects on PMTX induced nephrotoxicity increasing antioxidant activity and reducing oxidative damage.